Restoring the Coastal Environment in Cartagena, Colombia - World Bank (Washington, DC, 2014)
Cartagena, the historic city where the '1983 Cartagena convention for the Protection of the Caribbean' was signed, is meeting its responsibilities to protect the public health of its citizens as well as the costal marine environment through improved wastewater management. Cartagena's experience can serve as an inspiration to the wider Caribbean region and provide a model for other developing coastal cities. Water pollution control is a key issue for the world's coastal cities. Pollution emanating from domestic and industrial wastewater can not only contaminate the ocean environment but also damage highly productive estuaries and bays that provide a critical ecological connection to the marine environment. Inadequate wastewater management can also pollute urban beaches, potentially threatening public health and undermining tourism. This technical note summarizes Cartagena's experience in wastewater management for international dissemination and was jointly prepared by the World Bank, the Colombian Ministry of Environment and Sustainable Development, the Cartagena water utility (ACUACAR), and the Global Partnership for the Oceans (GPO).